Continuity in the parameter for the solutions of one-dimensional boundary-value problems for differential equations of higher orders in Slobodetsky spaces - Maslyuk, H. O.; Mikhailets, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We introduce the most general class of linear boundary-value problems for systems of ordinary differential equations oforder $r ≥ 2$ whose solutions belong to the Slobodetsky space $^{Ws+r}_p\bigl( (a, b),C_m\bigr),$ where $m \in N,\; s > 0$ and $p \in (1,∞ )$.We also establish sufficient conditions under which the solutions of these problems are continuous functions of the parameterin the Slobodetsky space $W^{s+r}_p\bigl( (a, b),C_m\bigr)$.